Public health vulnerability to wintertime weather: time-series regression and episode analyses of national mortality and morbidity databases to inform the Cold Weather Plan for England. (August 2016) - Hajat, S.; Chalabi, Z.; Wilkinson, P.; Erens, B.; Jones, L.; Mays, N.
Abstract: Objectives: To inform development of Public Health England's Cold Weather Plan (CWP) by characterizing pre-existing relationships between wintertime weather and mortality and morbidity outcomes, and identification of groups most at risk. Study design: Time-series regression analysis and episode analysis of daily mortality, emergency hospital admissions, and accident and emergency visits for each region of England. Methods: Seasonally-adjusted Poisson regression models estimating the percent change in daily health events per 1 °C fall in temperature or during individual episodes of extreme weather. Results: Adverse cold effects were observed in all regions, with the North East, North West and London having the greatest risk of cold-related mortality. Nationally, there was a 3.44% (95% CI: 3.01, 3.87) increase in all-cause deaths and 0.78% (95% CI: 0.53, 1.04) increase in all-cause emergency admissions for every 1 °C drop in temperature below identified thresholds. The very elderly and people with COPD were most at risk from low temperatures. A&E visits for fractures were elevated during heavy snowfall periods, with adults (16–64 years) being the most sensitive age-group. Since even moderately cold days are associated with adverse health effects, by far the greatest health burdens of cold weather fell outside of the alert periods currently used in the CWP. Conclusions: Our findings indicate that levels 0 ('year round planning') and 1 ('winter preparedness and action') are crucial components of the CWP in comparison to the alerts. Those most vulnerable during winter may vary depending on the type of weather conditions being experienced. Recommendations are made for the CWP. Highlights: Following recent harsh winters, a National Cold Weather Plan (CWP) for England was introduced in 2011. This paper documents epidemiologic assessment of retrospective data undertaken as part of an evaluation of the CWP. There was a 3.44% (95% CI: 3.01, 3.87) increase in all-cause deaths per 1 °C drop in temperature below thresholds. The elderly are most vulnerable, however younger adults were at greatest risk of A&E visits for fractures during heavy snow. By far the greatest health burdens of cold weather fall outside of the alert periods currently used in the CWP.